1995
DOI: 10.1016/0029-7844(95)00246-n
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Carbohydrate-Rich Beverage on Mood, Appetite, and Cognitive Function in Women With Premenstrual Syndrome

Abstract: The results suggest that the psychological and appetitive symptoms of PMS can be relieved after consuming a specially-formulated, carbohydrate-rich beverage known to increase serum tryptophan levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…For instance, carbohydrate intake is most frequently found to improve mood in sub-clinical subjects suffering from carbohydrate-craving obesity, late luteal phase syndrome or seasonal affective disorders (e.g. Wurtman and Wurtman 1984;Lieberman et al 1986;Rosenthal et al 1989;Wurtman et al 1989;Steinberg et al 1994;Sayegh et al 1995). In non-clinical subjects, however, beneficial mood effects of carbohydrates are less consistent, revealing either no effects on mood (Smith et al 1988;Deijen et al 1989;Reid et al 1995;Wells et al 1998) or slight and contradictory alterations in feelings of calmness, tension, and fatigue (e.g.…”
Section: Dietary Depletion Of Brain Serotonin: Acute Tryptophan Deplementioning
confidence: 96%
“…For instance, carbohydrate intake is most frequently found to improve mood in sub-clinical subjects suffering from carbohydrate-craving obesity, late luteal phase syndrome or seasonal affective disorders (e.g. Wurtman and Wurtman 1984;Lieberman et al 1986;Rosenthal et al 1989;Wurtman et al 1989;Steinberg et al 1994;Sayegh et al 1995). In non-clinical subjects, however, beneficial mood effects of carbohydrates are less consistent, revealing either no effects on mood (Smith et al 1988;Deijen et al 1989;Reid et al 1995;Wells et al 1998) or slight and contradictory alterations in feelings of calmness, tension, and fatigue (e.g.…”
Section: Dietary Depletion Of Brain Serotonin: Acute Tryptophan Deplementioning
confidence: 96%
“…Since the mood symptoms are most severe and common signs of PMS, in the first step, we can use the suggestive treatments like carbohydrate foods. Like the inhibitor drugs, these foods enhance the reuptake of serotonin and cause increase of serotonin in the brain (Sayegh et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…There is also one study demonstrating that women with severe PMS significantly increased their carbohydrate intake relative to women without PMS [49]. Furthermore, improved mood and a reduction in PMS symptoms have been reported with high carbohydrate intake in women with PMS [50]. Theoretically, increasing dietary carbohydrates may increase tryptophan availability and potentially elevate brain serotonin levels.…”
Section: Implications Of Ssris For Women With Diabetesmentioning
confidence: 95%
“…A few studies have reported that nondiabetic women increase the amount of carbohydrates selected during the luteal phase of their menstrual cycle [48][49][50]. There is also one study demonstrating that women with severe PMS significantly increased their carbohydrate intake relative to women without PMS [49].…”
Section: Implications Of Ssris For Women With Diabetesmentioning
confidence: 95%